Effect of establishing arteriovenous fistula on left ventricular myocardial function in uremic patients - Ai-qing Chen; Yong Chen (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To employ two dimensional speckle tracking imaging （2D-STI） and non-invasive left ventricular pressure-strain loop for observing and evaluating the changes of left ventricular myocardial function of patients with end-stage renal disease （ESRD） during early establishment of autogenous arteriovenous fistula （AVF）. Methods A total of 55 ESRD patients who were to undergo AVF surgery in the Department of Nephrology, Subei People's Hospital from October 1, 2022 to March 31, 2023 were selected. Echocardiography was performed at Week 1 pre-operation, Day 1 post-operation and Week 6 post-operation. The changes of global longitudinal strain （GLS） and myocardial work （MW） were compared at different timepoints pre/post-AVF. Sensitivity and correlation of myocardial work （MW） were examined for global work efficiency （GWE）, global work index （GWI）, global wasted work （GWW）, global constructive work （GCW） and global longitudinal strain （GLS）. Results Absolute values of GWE （P = 0.025） and GLS （P＜0.001） rose and GWW （P = 0.041） declined at Day 1 post-AVF. Absolute values of GWI （P = 0.003, P = 0.001）, GWE （P = 0.005, P＜0.001） and GLS （P = 0.026, P＜0.001） at Week 6 post-operation were lower than those at Week 1 pre-operation and Day 1 post-operation while GWW rose （P＜0.001, P＜0.001）. Meanwhile area under ROC curve of GLS was 0.607. It was smaller than that of GWI/GWW/GWE （0.612, 0.657 & 0.618）. Correlation analysis indicated that GLS was correlated negatively with GWI/GCW/GWE （r = −0.629; r = −0.574; r = −0.659; all P＜0.05） and positively with GWW （r = 0.418; P＜0.05）. Conclusion In ESRD patients, left ventricular myocardial function becomes transiently elevated at the start of AVF establishment. After some time, impairment is lessened. As compared with 2D-STI /LVEF, non-invasive LVPSL may effectively evaluate the changes of left ventricular myocardial function during early AVF establishment in ESRD patients.